Tuberculosis treatment outcomes and associated factors in two states in Nigeria
Objective: To determine the treatment success rate among TB patients and associated factors in Anambra and Oyo, the two states with the largest burden of tuberculosis in Nigeria. Methods: A health facility record review for 2016 was conducted in the two states (Anambra and Oyo). A checklist was used to extract relevant information from the records kept in each of selected DOTS facilities to determine TB treatment success rates. Treatment success rate was defined as the proportion of new smear-positive TB cases registered under DOTS in a given year that successfully completed treatment, whether with bacteriologic evidence of success (“cured”) or without (“treatment completed”). Treatment success rate was classified into good (≥85%) and poor (<85%) success rates using the 85% national target for TB treatment outcome. Data were analysed using descriptive statistics and Chi square at p<0.05. Results: There were 1281 TB treatment enrollees in 2016 in Anambra and 3809 in Oyo (total=4835). An overall treatment success rate of 75.8% was achieved (Anambra-57.5%; Oyo-82.0%). The percentage cure rates were 61.5% for Anambra and 85.2% for Oyo. Overall, only 28.6% of the facilities in both states (Anambra-0.0%; Oyo-60.0%) had a good treatment success rate. More facilities in Anambra (100.0%) than Oyo (40.0%) had a poor treatment success rate (p<0.001), as did more private/FBO (100.0%) than public health facilities (60.0%) (p=0.009). All tertiary facilities had a poor treatment success rate followed by 87.5% of secondary health facilities and 56.5% of primary healthcare facilities (p=0.035). Conclusion: Treatment success and cure rates in Anambra state were below the 85.0% of the recommended target set by the WHO. Geographical location, and level/tier and type of facility were factors associated with this. Interventions are recommended to address these problems.